Translation of Complex Occasionalisms in Modern English Novels - E. V. Lartseva; Yu. R. Gafurova (Научный диалог)
Composite occasionalism is understood as a new formation, which is based on a syntactic complex acting as a multicomponent unity and characterized by a hyphenated connection of elements (for example, how-to-win-that-job articles, last-Friday-before-a-vacation feeling). The ways of translating complex occasionalisms in modern English-language novels into Russian are discussed in the article. The results of a comparative analysis on the material of five novels and their Russian translations are presented: “White Teeth” by Z. Smith (2000) — “Belye zuby” (translated by O. L. Kachanova, M. A. Melnichenko, 2005), “About beauty” by Z. Smith (2005) — “O krasote” (translated by O. L. Kachanova, A. N. Vlasova, 2010), “Do you know how to keep secrets?” by S. Kinsella (2003) — “A ty umeesh khranit’ sekrety?” (translated by T. A. Pertseva, 2019), “Love, Rosie” by S. Ahern (2005) — “Ne veryu. Ne nadeyus’. Lyublyu” [“I don’t believe. I hope not. I love”] (translated by V. I. Lavronenko, 2009) and “Juliet, Naked” by N. Hornby (2009) — “Golaya Dzhulyetta” (translated by Yu. A. Balayan, 2010). The following translation techniques were reviewed: descriptive translation with the loss of lexical “condensation”, calquing, replacement of a complex occasional unit in one word, graphic-punctuation transfer, omission of the occasional unit in the translation text or its incomplete transfer.